STUDY OF SUSPENDED SEDIMENT DISTRIBUTION USING NUMERICAL MODEL AND SATELLITE DATA IN BENOA BAY-BALI, INDONESIA - I Gede Hendrawan; Koji Asai (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2008)
The distribution of suspended sediment and its concentration within Benoa bay was calculated by a numerical model and utilization of satellite data. A two-dimensional coupled hydrodynamic-transport model for the distribution characteristics of suspended sediment within the bay is presented here. Three-river discharges and sewerage installation outlets were used as source points of the suspended sediment. The model result showing the distribution of suspended sediment pattern follows the tidal level dynamic. It is concerned to the current pattern generated by tidal. The ALOS/AVNIR-2 satellite data also have good capability to investigate the suspended sediment distribution in coastal area. By using visible channels and developed regression of Digital Number (DNs) of AVNIR-2 data and observation data, the distribution of suspended sediment in Benoa bay was generated. Numerical model and satellite data quantitatively have the same tendency, but slightly different value. It is because of the differences in pollutant sources point. Keywords: Numerical model, satellite data, suspended sediment